End user characteristics in promoting maintenance culture within shared facilities - Nor Zaimah Che-Ghani,; Nik Elyna Myeda,; Azlan Shah Ali, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Stratified residential building is related to shared community area where the facilities are being shared among neighborhood. Thus, it requires responsible and considerate attitude to buildings, public facilities and environment. Various problems have continued to arise in the management of stratified residential buildings due to lack of standard guidelines and professionalism which lead to low quality of service performance. One of the contributing factors in performance of maintenance services is the uncontrollable of end user characteristics. So, this paper aims to investigate the relationship of the end user characteristics and their satisfaction towards maintenance performance. To achieve the objectives of the study, a set of questionnaire surveys were distributed to the residents (end users) of stratified residential building in Klang Valley. The constructs for end user characteristics are prevention of vandalism, regulation and compliance, use and accessibility to the property, reporting and response problems and demand and expectation of end user. Whereas, the constructs for user satisfaction namely waiting time response for maintenance staff, waiting period to request repairs, worth of maintenance fee, frequency of failure, staff professionalism and overall satisfaction. Results of this study concluded that the relationship between end user characteristics and satisfaction towards maintenance performance are significant. This paper proposes that to enhance the performance of service maintenance in shared area like stratified residential building, adopting and practicing maintenance culture within end users are a stepping stone to produce effective operation and maintenance management in future.